2007
DOI: 10.5059/yukigoseikyokaishi.65.119
|View full text |Cite
|
Sign up to set email alerts
|

Total Syntheses of FR901464

Abstract: : Three total syntheses of potent anticancer natural product FR901464 are described. The first total synthesis by the Jacobsen group used transition metal-catalyzed reactions to prepare their chiral fragments. Subsequently, the Kitahara group described their synthesis using the chiral pool to construct their building blocks. Finally, the Koide group published the most recent synthesis of FR901464 using both asymmetric reactions and the chiral pool for their chiral fragment syntheses.It is envisioned that these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…For comparison, the literature contains only one report of an active carbamate PD analogue ( 2 ), which is 4-fold less active than pladienolide B . It is noted that despite several very high quality total syntheses, ,,,, the complexity of 1 has hindered development of extensive SAR data, and there have been no reports on the activity of corresponding 1 reference compounds to compare to most of the analogues in Scheme . For example, there are no reports on the synthesis, or bioactivity, of carbamate analogues of 1 to directly compare to carbamates 7 − 10 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For comparison, the literature contains only one report of an active carbamate PD analogue ( 2 ), which is 4-fold less active than pladienolide B . It is noted that despite several very high quality total syntheses, ,,,, the complexity of 1 has hindered development of extensive SAR data, and there have been no reports on the activity of corresponding 1 reference compounds to compare to most of the analogues in Scheme . For example, there are no reports on the synthesis, or bioactivity, of carbamate analogues of 1 to directly compare to carbamates 7 − 10 .…”
Section: Resultsmentioning
confidence: 99%
“…There have been numerous synthetic approaches to 1 ; ,, however, since these approaches target the much more complex natural product, they were not highly instructive for the synthetic targets 3a , 3b , and 3c . Our approach to these concise analogues provided compounds 3a , 3b , and 3c enantioselectively and diasterospecifically in a highly step-efficient manner .…”
Section: Introductionmentioning
confidence: 99%
“…Exceptional biological activity of FR901464 and spliceostatin A has attracted considerable interest from the synthetic community. 6 In 2000, the first total synthesis of FR901464 was reported by Jacobsen and co-workers using an asymmetric hetero-Diels–Alder reaction as the key transformation. 7 The synthesis was accomplished in the longest linear sequence of 19 steps (40 total steps).…”
Section: Introductionmentioning
confidence: 99%
“…These were disclosed first by Jacobsen and co-workers (40 steps), utilizing a powerful asymmetric hetero Diels–Alder reaction to form the two tetrahydropyrans, and shortly thereafter by Kitahara (41 steps), enlisting the chiral pool to access the two tetrahydropyrans. Subsequent total syntheses by Koide (28 steps) and later by Ghosh (22 steps) provided more expedient assembly of the two highly substituted and functionalized tetrahydropyran rings . In addition to demonstrating the critical role of the epoxide, Jacobsen defined the instability of FR901464 and further showed that removal of the right-hand subunit tertiary alcohol not only abrogated this instability, but also enhanced biological potency .…”
mentioning
confidence: 98%
“…In an extension of these observations, Koide later found that replacement of the tertiary alcohol with a methyl group (vs H) not only avoided the rapid compound degradation but also improved potency as much as 100-fold . Such synthetic analogues, named the meayamycins (Figure ), represented an early contribution to the growing number of natural products and analogues in the class accessed by total synthesis. In 2007, Yoshida disclosed that FR901464 binds a subunit of the spliceosome disrupting conversion of pre-mRNA to mRNA . Shortly thereafter, Koide established that the meayamycins act in an analogous manner .…”
mentioning
confidence: 99%